ECONOMIC ANALYSIS OF ORGANIC GINGER FARMING IN LONGLENG DISTRICT: A CASE STUDY PONGO, YONGNYAH, YONGAM AND BHUMNYU VILLAGE - Chubakumzuk Jamir (Institute of Computer Science (IOCS), 2022)
Ginger (Zingiber officinale Rosc.) is an herbaceous perennial crop usually grown as an annual for its rhizome. It is a valuable cash crop does not only serve as integral medium for food security, but also as a source of income generation, and employer of labour in the producing areas of Longleng. Lack of finance, inadequate farm inputs, storage facilities and high cost of labour are identified as the primary constraints to organic ginger production in the region. Research survey of farmers producing organic ginger was conducted in 2022 in Pongo, Yongnyah, Yonyam and Bhumnyu villages. Total of thirty (30) organic ginger producers were selected using random sampling methods from each of the four villages with a total sample size of one hundred twenty (120). The results revealed that the organic ginger production was profitable on cash cost basis (BCR 1.75). Seed have major cost share for ginger production (65.1%). The estimated coefficients of Cobb-Douglas production function showed that seed, labour and number of years for crop rotation were the significant factors for organic ginger production. The study concluded that ginger production can be made viable enterprise with increased focus on conducive environment and investment climate by subsidising farm inputs and providing affordable loans to the smallholder farmers for a sustainable production. The study pointed out that the organic ginger farming could be a highly beneficial and market-oriented activity in Longleng. It also points out the problems faced by the organic ginger farmers and finally suggests policy implication.